The frail patient undergoing cardiac surgery: lessons learned and future perspectives - Pozzi, Matteo; Mariani, Silvia; Scanziani, Margherita; Passolunghi, Davide; Bruni, Adriana; Finazzi, Alberto; Lettino, Maddalena; Foti, Giuseppe; Bellelli, Giuseppe; Marchetto, Giovanni (Frontiers in Cardiovascular Medicine, 2023)
Frailty is a geriatric condition characterized by the reduction of the individual's homeostatic reserves. It determines an increased vulnerability to endogenous and exogenous stressors and can lead to poor outcomes. It is an emerging concept in perioperative medicine, since an increasing number of patients undergoing surgical interventions are older and the traditional models of care seem to be inadequate to satisfy these patients' emerging clinical needs. Nowadays, the progressive technical and clinical improvements allow to offer cardiac operations to an older, sicker and frail population. For these reasons, a multidisciplinary team involving cardiac surgeons, clinical cardiologists, anesthesiologists, and geriatricians, is often needed to assess, select and provide tailored care to these high-risk frail patients to optimize clinical outcomes. There is unanimous agreement that frailty assessment may capture the individual's biological decline and the heterogeneity in risk profile for poor health-related outcomes among people of the same age. However, since commonly used preoperative scores for cardiac surgery fail to capture frailty, a specific preoperative assessment with dedicated tools is warranted to correctly recognize, measure and quantify frailty in these patients.On the contrary, pre-operative and post-operative interventions can reduce the risk of complications and support patient recovery promoting surgical resilience.Minimally invasive cardiac procedures aim to reduce surgical trauma and may be associated with better clinical outcome in this specific sub-group of high-risk patients. Among postoperative adverse events, the occurrence of delirium represents a risk factor for several unfavorable outcomes including mortality and subsequent cognitive decline. Its presence should be carefully recognized, triggering an adequate, evidence based, treatment. There is evidence, from several cross-section and longitudinal studies, that frailty and delirium may frequently overlap, with frailty serving both as a predisposing factor and as an outcome of delirium and delirium being a marker of a latent condition of frailty.In conclusion, frail patients are at increased risk to experience poor outcome after cardiac surgery. A multidisciplinary approach aimed to recognize more vulnerable individuals, optimize pre-operative conditions, reduce surgical invasivity and improve post-operative recovery is required to obtain optimal longterm outcome.